Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To do elimination, you combine the two equations by adding
-9x + y = 16
+ x - y = 0
-8x + 0y = 16
Now that there are 0y, we can solve for x:
-8x = 16
divide both sides by -8
x = -2
To solve for y, plug the answer you got for x in to the original equations.
-9x + y = 16
-9(-2) + y = 16
18 + y = 16
y = -2
x - y = 0
-2 - y = 0
y = -2
x = -2 and y = -2
-9x + y = 16
+ x - y = 0
-8x + 0y = 16
Now that there are 0y, we can solve for x:
-8x = 16
divide both sides by -8
x = -2
To solve for y, plug the answer you got for x in to the original equations.
-9x + y = 16
-9(-2) + y = 16
18 + y = 16
y = -2
x - y = 0
-2 - y = 0
y = -2
x = -2 and y = -2
-9x+y=16
x-y=0
add the two equations, the y's cancel each other out
-8x=16
divide by -8
x=-2
x-y=0
add the two equations, the y's cancel each other out
-8x=16
divide by -8
x=-2
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.